2019
DOI: 10.1016/j.ajog.2018.11.829
|View full text |Cite
|
Sign up to set email alerts
|

806: Virtual reality may decrease pain during labor

Abstract: across three groups: small-for-gestational age (SGA) (BW <10%ile), appropriate-for-gestational age (AGA) (BW 10-90%ile), and largefor-gestational age (LGA) infants (BW >90%ile), with SGA as the reference group. Interval-censored regression estimated median duration of labor stratified by actual BW, as well as by labor type (spontaneous vs. induction) and parity (nulliparity vs. multiparity). RESULTS: Of 17,099 women, 5970 (34.9%) were induced and 6,457 (37.8%) were nulliparous; 2,457 (14.4%) and 908 (5.3%) wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
5

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 0 publications
3
10
0
5
Order By: Relevance
“…One of the cornerstones of healthcare improvement, as formulated by the Institute of Healthcare Improvement, is with respect to the enhancement of patient experience 32 . In this regard, the findings of our pilot remain promising and in-line with other pregnancy-related studies which have demonstrated a high level of www.nature.com/scientificreports www.nature.com/scientificreports/ maternal satisfaction and acceptability for VR, with approval ratings between 77-82% 17,33 . This alludes to women being interested in and welcoming the addition of the technological medium into their pregnancy care.…”
Section: Discussionsupporting
confidence: 84%
“…One of the cornerstones of healthcare improvement, as formulated by the Institute of Healthcare Improvement, is with respect to the enhancement of patient experience 32 . In this regard, the findings of our pilot remain promising and in-line with other pregnancy-related studies which have demonstrated a high level of www.nature.com/scientificreports www.nature.com/scientificreports/ maternal satisfaction and acceptability for VR, with approval ratings between 77-82% 17,33 . This alludes to women being interested in and welcoming the addition of the technological medium into their pregnancy care.…”
Section: Discussionsupporting
confidence: 84%
“…Ze studií (10,11,1,12,13) vyplývá pozitivní vliv virtuální reality jako nefarmakologické metody v péči o ženy s porodní bolestí v I. době porodní, ale i při ošetření epiziotomie a v poporodním období. Ženy při využití této metody hodnotily pozitivněji zvládání samotného porodu, porodní bolesti a byly více spokojeny s péčí porodní asistentky, zdravotnického personálu.…”
Section: Výsledkyunclassified
“…Ženy při využití této metody hodnotily pozitivněji zvládání samotného porodu, porodní bolesti a byly více spokojeny s péčí porodní asistentky, zdravotnického personálu. Data ukazují, že významným faktorem podílejícím se na rozvoji porodní bolesti je strach a úzkost (10).…”
Section: Výsledkyunclassified
See 2 more Smart Citations